The fate of private international contracts under the imposition of a health emergency due to the spread of the emerging Corona virus (Covid-19) - A reading of Moroccan and comparative law - Jamal Elkhammar (International Review of Law, 2021)
Nowadays, humanity is living a global event that affected all levels of life and changed all plans. The Corona pandemic, came to remind us about our weaknesses and our lack of resourcefulness in the social and economic sectors. Hence, this made us face legal risks in light of this deadly epidemic, which affects the health of people and endangers their lives.